Newly-generated Al(OH)3-supported Pd nanoparticles-catalyzed Stille and Kumada coupling reactions of diazonium salts, (Het)aryl chlorides. Issue 1 (7th January 2016) - Li, Xing; Zhu, Tingting; Shao, Zhongqi; Li, Yingjun; Chang, Honghong; Gao, Wenchao; Zhang, Yongli; Wei, Wenlong
Abstract: A ligand-free Pd/Al(OH)3 nano-catalyst which is prepared by one-pot three-component method using Pd(PPh3 )4, tetra (ethylene glycol), and aluminum tri- sec -butoxide exhibits excellent catalytic activity in Stille cross-couplings of (Het)aryl chlorides, arenediazonium tetrafluoroborate salts with phenyltributylstannane, respectively, and Kumada couplings of (Het)aryl chlorides with various Grignard reagents. More importantly, these two processes show excellent functional group compatibility with moderate to good yields and they are also versatile with respect to not only (Het)aryl chlorides, but also diazonium salts, and heteroaryl Grignard reagents. The nano-catalyst could also be recycled and reused5 times without loss of activity and decrease of yield. Graphical abstract: